Effects of different seat inclination angles on lumbar dynamic response and injury during lunar-earth reentry - Jin, Mengmeng; Wang, Jiatao; Zhou, Qianxiang; Guo, Pan; Zhang, Jingfei; Wang, Yi (Frontiers in Bioengineering and Biotechnology, 2024)
The inclination angle of the spacecraft seat is related to the astronaut's reentry angle, which in turn affects the safety of the astronauts. This study quantitatively analyzed the effects of different seat inclination angles on astronauts' lumbar spine injuries using the finite element method during the Lunar-Earth reentry. Firstly, a finite element model of the astronaut's lumbar spine was constructed based on reverse engineering technology, and the effectiveness of the model was verified through mesh sensitivity, vertebral range of motion, and spinal impact experiments. Then, simulation calculations were carried out for different seat inclination angles (0°, 10°, 20°, and 30°) under the typical reentry return loads of Chang'e 5T1 (CE-5T1) and Apollo 10, and the prediction and evaluation of lumbar spine injuries were conducted in conjunction with the biological tissue injury criteria. The results indicated that the stress on the vertebrae and annulus fibrosus increased under both reentry loads with the rise of the seat inclination angle, but the increasing rates decreased. When the acceleration peak of CE-5T1 approached 9G, the risk of tissue injury was higher under the seat angle exceeded 20°. According to the Multi-Axis Dynamic Response Criteria for spinal injury, neither of the two load conditions would directly cause injury to the astronauts' lumbar spine when the seat inclination angle was below 30°. The study findings provide a numerical basis for designing and improving the spacecraft's inclination angle in crewed lunar missions, ensuring the safety of astronauts.